Awareness of Medico-Legal Aspects and Documentation amongst Health Professionals in a Tertiary Care Hospital (Medico Legal Update, 2019)
Background: The professionals working in a hospital, especially the clinical staff will have to deal withmany medical cases which have legal implications. Health care providers are at high risk for litigations.Being aware about medico legal aspects and importance of documentation and performing their dutiesethically can safeguard themselves against risks of litigation. Objective: To assess the awareness amonghealth professionals about legal practices and medical documentation in patient care. Method: A crosssectionalstudy was carried out with the help of a validated and pre-tested questionnaire involving 219health professionals belonging to different disciplines of allied health sciences and nursing at a tertiarycare hospital in south India. Result: The study showed that the professionals who were involved indirectly,such as pharmacists and health information management professionals scored less than 50% of the totalknowledge score while those involved in direct clinical care such as physiotherapists and nurses scored morethan 50% of the total knowledge score, and hence better. Similarly professional with three or more yearsof experience scored above 50% and hence better than professionals with lesser experience. The responsesindicated that, the respondents were only able to attain a score around 50% of the maximum attainable.Conclusion: The findings indicate there is a need of bringing on the awareness about the various aspects ofmedico-legal cases in patient care. This is not only for professional safety but also for the safety of patientsat large. Hospital and their administrators should regularly conduct sensitisation programs on medico legalaspects in patient care and importance of documentation